Speak Mandarin campaign in the 21st century : examining the awareness and attitudes of NTU undergraduates. - Foo, Sheryl Yunwen. (2008)
Examination of two research areas: awareness and attitudes of a fragmented yet vital public of the 1979-launched annual Speak Mandarin Campaign (SMC), which is designed to promote Mandarin in place of dialects and subsequently to encourage English-speaking Chinese to learn Mandarin.